PENGARUH E-FILING, SOSIALISASI, KESADARAN WAJIB PAJAK, DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - I Gusti Agung Prama Yoga; Tjokorda Istri Agung Lita Apriliana Dewi (KRISNA: Kumpulan Riset Akuntansi, 2022)
This study aims to research the implementation of e-Filing, tax socialization, taxpayer awareness and tax sanctions partially and simultaneously on individual taxpayer compliance. The location of this research is at East Denpasar Primary Tax Office. The population uses individual taxpayers at East Denpasar Primary Tax Office and 100 respondents for samples . Data analysis technique using Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination Test, F Test and t Test. From the results of study obtained the results: 1) the effect of e-Filing aplication has a positive and not significant effect, where the t-count is 1.268 and the significance value is 0.208, 2) the tax socialization has positive and insignificant effect, where the t-count value is 0.131 and the significance value is 0.896. 3) taxpayer awareness has significant positive effect on individual taxpayer compliance, where the t-count value is 3.138 and the significance value is 0.002. and 4) tax sanctions have a significant positive effect on individual taxpayer compliance, where the t-count value is 5.586 and the significance value is 0.000. The magnitude of independent variables on individual taxpayer compliance is 58.4%. Keywords: e-Filing, Tax Socialization, Taxpayer Awareness, Tax Sanctions and Individual Taxpayer Compliance